Will they Sing the Same Tune? : Measuring Convergence in the new European System of Financial Supervisors - Quintyn, Marc (IMF Working Papers; Working Paper ;, 2009)
In June 2009 a new financial supervisory framework for the European Union (EU) was endorsed, consisting of a macro- and a micro-prudential pillar. The latter is composed of a Steering Committee, a supranational layer and a network of national supervisory authorities at the bottom, de facto establishing a complex multiple principals-multiple agents network. This paper focuses on the network of national agencies. Starting from an analysis of supervisory architectures and governance arrangements, we assess to what extent lack of convergence could undermine efficient and effective supervision. The main conclusion is that harmonization of governance arrangements towards best practice would better align supervisors' incentive structures and, hence, be beneficial for the quality of supervision.